OP0125 LYMPHOMAS COMPLICATING RHEUMATOID ARTHRITIS: RESULTS OF A FRENCH MULTI-CENTRE CASE-CONTROL STUDY. (2nd June 2020) - Kedra, J.; Seror, R.; Dieudé, P.; Constantin, A.; Toussirot, E.; Kfoury, E.; Masson, C.; Cornec, D.; Dubost, J. J.; Marguerie, L.; Ottaviani, S.; Grados, F.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is associated with an increased risk of non-Hodgkin B-cell lymphoma (B-cell NHL). Objectives: 1)To study the characteristics of B-cell NHL complicating RA 2)To identify the factors associated with their occurrence. Methods: A multi-centre case-control study was performed in France. Cases were patients with RA fulfilling the ACR-EULAR 2010 criteria, who developed a B-cell NHL after the diagnosis of RA. Cases were reported following a call for observations by the "Club Rhumatismes et Inflammation" network, registries from the French society of Rheumatology (AIR, ORA and REGATE) and the ESPOIR cohort. For each case, 2 control patients were drawn at random from patients in the ESPOIR cohort with RA fulfilling the ACR-EULAR 2010 criteria; cases and controls were matched on age (age at lymphoma diagnosis for cases and age at the 10-year ESPOIR visit for controls). Patients with associated Sjögren's syndrome were excluded. Cases and controls characteristics were compared for parameters associated with the occurrence of lymphoma. Results: A total of 54 cases were included and matched to 108 controls. Lymphomas were mostly diffuse large B-cell lymphomas (n=26, 48.2%) (Figure 1 ). EBV positivity was found in 4 cases among 27 tested (14.8%). Cases had a mean age of 63.5 years (SD=10.9), and had a mean RA duration of 12.4 years (SD=10.5) at the time of diagnosis of lymphoma; there was no significant difference with controls (p=0.47 and p=0.40 respectively). The mean duration of follow-up after the diagnosis of lymphoma was 5.2 years (SD=5.8). In univariate analysis, factors associated with occurrence of B-cell NHL were: male gender (OR=3.3, 95%CI: 1.7-6.7), positive ACPA (OR=5.1, 95%CI: 2.0-15.7), positive Rheumatoid Factor (RF) (OR=3.9, 95%CI=1.6-12.2), erosions on X-rays (OR=15.4, 95%CI: 6.9-37.7) and DAS28 (OR=2.0, 95%CI: 1.5-2.7). Methotrexate, TNF-blockers and the number of previous biologics were not associated with the occurrence of B-cell NHL. Hydroxychloroquine and sulfasalazine were more frequent in cases versus control, which could be linked to a date bias. Erosions and DAS28 remained significant in multivariate analysis (Table 1 ). Conclusion: This study revealed an association between markers of activity (DAS28), severity (erosions) and autoimmune B-cell activation (RF and ACPA) and the risk of B-cell NHL in patients with RA, supporting the continuum between autoimmunity and lymphomagenesis in RA. Disclosure of Interests: Joanna KEDRA: None declared, Raphaèle Seror Consultant of: BMS UCB Pfizer Roche, Philippe Dieudé: None declared, Arnaud Constantin: None declared, ERIC TOUSSIROT: None declared, Elias Kfoury: None declared, Charles Masson: None declared, Divi Cornec: None declared, Jean-Jacques Dubost: None declared, Laurent Marguerie: None declared, Sebastien Ottaviani: None declared, Franck Grados: None declared, Rakiba Belkhir: None declared, olivier fain: None declared, Philippe Goupille Grant/research support from: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Consultant of: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Speakers bureau: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Christelle Sordet: None declared, Bruno Fautrel Grant/research support from: AbbVie, Lilly, MSD, Pfizer, Consultant of: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Lilly, Janssen, Medac MSD France, Nordic Pharma, Novartis, Pfizer, Roche, Sanofi Aventis, SOBI and UCB, Peggy Philippe: None declared, Muriel PIPERNO: None declared, Bernard Combe Grant/research support from: Novartis, Pfizer, Roche-Chugai, Consultant of: AbbVie; Gilead Sciences, Inc.; Janssen; Eli Lilly and Company; Pfizer; Roche-Chugai; Sanofi, Speakers bureau: Bristol-Myers Squibb; Gilead Sciences, Inc.; Eli Lilly and Company; Merck Sharp & Dohme; Pfizer; Roche-Chugai; UCB, Olivier Lambotte Consultant of: BMS France, MSD, Astra Zeneca, Incyte, Christophe Richez Consultant of: Abbvie, Amgen, Mylan, Pfizer, Sandoz and UCB., Jérémie SELLAM: None declared, Thomas Sene: None declared, Guillaume Denis: None declared, Thierry Lequerre: None declared, Xavier Mariette Consultant of: BMS, Gilead, Medimmune, Novartis, Pfizer, Servier, UCB, Gaetane Nocturne: None declared